Pengaruh Capital Adequacy Ratio (CAR), Financing To Deposit Ratio (FDR), Non Performing Financing (NPF) dan Inflasi Terhadap Profitabilitas (Studi Kasus PT Bank Victoria Syariah Periode September 2013-2018) - Margibi Misuari; Rafika Rahmawati (LPPM Universitas Islam 45, 2022)
This research aims to know the influence of Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), and Inflation against Profitability Return On Assets (ROA)at PT Bank Victoria Syariah. This study used a sample of Pt Victorian Sharia Bank, based on financial statements within the period for 6 years where the processed data is data per three months averaged starting in 2013 to 2018. The method used applies a quantitative approach to obtain data in the form of numbers so that the objectives in this study are achieved by using multiple linear regression analysis techniques. Results Empirical research shows that there is a simultaneous effect on the variables CAR, FDR, NPF, and inflation on profitability is measured with ROA at PT Bank Victoria Sharia. The results of this research also shows that the CAR . variable partially significant effect positive on profitability at PT Victoria Sharia Bank, while FDR, NPF and inflation variables do not affect profitability at PT Bank Victoria Syariah. Effect of CAR, FDR, NPF, and Inflation on bank profitability Victoria sharia is very influential, this is evidenced by the value of sig f 0.014 (p<0.05). Which means that the increasing CAR, FDR, NPF, and inflation will also increase the profitability (ROA) of bank victoria sharia.